Genetic Structure and Geographical Differentiation of Larix sibirica Ledeb. in the Urals - Chertov, Nikita; Vasilyeva, Yulia; Zhulanov, Andrei; Nechaeva, Yulia; Boronnikova, Svetlana; Kalendar, Ruslan (Multidisciplinary Digital Publishing Institute, 2022)
The Ural Mountains and the West Eurasian Taiga forests are one of the most important centers of genetic diversity for Larix sibirica Ledeb. Forest fragmentation negatively impacts forest ecosystems, especially due to the impact of their intensive use on the effects of climate change. For the preservation and rational use of forest genetic resources, it is necessary to carefully investigate the genetic diversity of the main forest-forming plant species. The Larix genus species are among the most widespread woody plants in the world. The Siberian larch (Larix sibirica, Pinaceae) is found in the forest, forest-tundra, tundra (Southern part), and forest-steppe zones of the North, Northeast, and partly East of the European part of Russia and in Western and Eastern Siberia; in the Urals, the Siberian larch is distributed fragmentarily. In this study, eight pairs of simple sequence repeat (SSR) primers were used to analyse the genetic diversity and population structure of 15 Siberian larch populations in the Urals. Natural populations in the Urals exhibit indicators of genetic diversity comparable to those of Siberia populations (expected heterozygosity, He = 0.623; expected number of alleles, Ne = 4017; observed heterozygosity, Ho = 0.461). Genetic structure analysis revealed that the examined populations are relatively highly differentiated (Fst = 0.089). Using various algorithms for determining the spatial genetic structure, the examined populations formed three groups according to geographical location. The data obtained are required for the development of species conservation and restoration programs, which are especially important in the Middle Urals, which is the region with strong forest fragmentation.